Granular Cell Tumor of the Toe: A Case Report - Federico Tamborini; Mario Cherubino; Stefano Scamoni; Luigi A. Valdatta (Hindawi Limited, 2010)
Granular cell tumor is a rare tumor of unknown etiology that more commonly affects the oral cavity but can also occur at other sites. The majorities of granular cell tumors are benign and present as a singular dermal nodule. We discuss a case of granular cell tumor of the fourth toe in a 54-year-old patient that was treated with conservative surgery, instead of amputation, and reconstruction with a dermal regeneration template.